2021
DOI: 10.1016/j.ajogmf.2021.100352
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's perspectives on severe acute respiratory syndrome coronavirus 2 vaccine

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
53
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
8
53
1
1
Order By: Relevance
“…Recent studies showed that the COVID-19 vaccine does not cause additional adverse effects in pregnant or lactating women [ 41 , 42 ]. However, surveys showed that only 28.2% of pregnant women in Italy were willing to get vaccinated [ 43 ]. This finding is in agreement with the observation that the scientific-sounding misinformation appears to be associated with the decline of the COVID-19 vaccine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the COVID-19 vaccine does not cause additional adverse effects in pregnant or lactating women [ 41 , 42 ]. However, surveys showed that only 28.2% of pregnant women in Italy were willing to get vaccinated [ 43 ]. This finding is in agreement with the observation that the scientific-sounding misinformation appears to be associated with the decline of the COVID-19 vaccine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 Currently, although vaccinal programs are opened to pregnant women, there are still reports of a poor acceptance rate in this category of patients. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Currently, although vaccinal programs are opened to pregnant women, there are still reports of a poor acceptance rate in this category of patients. 6,7 Indeed, SARS-CoV-2 infection has been reported to potentially affect the placenta. 8 Several reports suggest an increased risk of placental lesions due to hypoperfusion and inflammation in women with SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…This goal should be quickly reached, providing adequate information to the population on how to follow strict rules to seek hospital assistance, if and only a problem arises. Vaccines against SARS-COV-2 have now been produced and released; national societies recommend their use in pregnant women, [ 32 , 33 ] although preliminary reports show patients’ fear for eventual adverse events and safety concerns for the fetus [ 34 , 35 ]. Indeed, their diffusion will hopefully reduce the burden of the pandemic and consequently the impact on healthcare systems.…”
Section: Discussionmentioning
confidence: 99%